CXXC5 suppresses hepatocellular carcinoma by promoting TGF-β-induced cell cycle arrest and apoptosis. (21st October 2017) - Yan, Xiaohua; Wu, Jingyi; Jiang, Quanlong; Cheng, Hao; Han, Jing-Dong J; Chen, Ye-Guang
Abstract: Evading TGF-β-mediated growth inhibition is often associated with tumorigenesis in liver, including hepatocellular carcinoma (HCC). To better understand the functions and the underlying molecular mechanisms of TGF-β in HCC initiation and progression, we carried out transcriptome sequencing (RNA-Seq) to identify the target genes of TGF-β. CXXC5, a member of the CXXC-type zinc finger domain-containing protein family, was identified as a novel TGF-β target gene in Hep3B HCC cells. Knockdown of CXXC5 attenuated the expression of a substantial portion of TGF-β target genes and ameliorated TGF-β-induced growth inhibition or apoptosis of Hep3B cells, suggesting that CXXC5 is required for TGF-β-mediated inhibition of HCC progression. Analysis of the TCGA database indicated that CXXC5 expression is reduced in the majority of HCC tissue samples in comparison to that in normal tissues. Furthermore, CXXC5 associates with the histone deacetylase HDAC1 and competes its interaction with Smad2/3, thereby abolishing the inhibitory effect of HDAC1 on TGF-β signaling. These observations together suggest that CXXC5 may act as a tumor suppressor by promoting TGF-β signaling via a positive feedback loop, and reveal a strategy for HCC to bypass TGF-β-mediated cytostasis by disrupting the positive feedback regulation. Our findings shed new light on TGF-β signaling regulation and demonstrate the function of CXXC5 in HCC development.